Crop protection for resource-poor farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
a seminar on Crop Protection for Resource-poor Farmers. This was held from 4-8 November 1991 at the Isle of Thorns Conference Centre, University of Sussex, UK